2023
DOI: 10.21873/invivo.13106
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Thrombolysis for Treatment of Acute Life-threatening Pulmonary Embolism During Cesarean Section Followed by Post-partum Rescue Hysterectomy: A Case Report and Review of the Literature

Abstract: Background/Aim: Acute pulmonary embolism during cesarean section is extremely rare and only a limited number of cases have been reported in literature. The aim of this study was to report a case of acute high risk pulmonary embolism during elective cesarean section treated with systemic thrombolysis and discuss the multidisciplinary management in both early recognition and prompt treatment. Case Report: A 39-year-old, G5P2, ASA II parturient presented for repeat cesarean section under general anesthesia. A sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The modern management of PE includes anti-coagulation, thrombolysis, and surgical pulmonary embolectomy. The choice of management should be based on the patient’s status and the size of the thrombus clot [ 26 , 38 ]. However, no practical guidelines have been established for this difficult entity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modern management of PE includes anti-coagulation, thrombolysis, and surgical pulmonary embolectomy. The choice of management should be based on the patient’s status and the size of the thrombus clot [ 26 , 38 ]. However, no practical guidelines have been established for this difficult entity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the risks and benefits of this drug administration are still controversial due to the risk of thrombosis [ 55 57 ]. Karakosta et al have recently reported a case of uterine conservation after acute life-threatening PE during C-Section which required postpartum rescue hysterectomy due to massive bleeding [ 26 ]. Initial uterine conservation carries the risk of subsequent emergency hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation